Pengaruh Literasi Keuangan, Locus of Control, dan Pendapatan Orang Tua terhadap Perilaku Manajemen Keuangan Mahasiswa Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram - Ika Nurfitriani; Nur Fitriyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This research is motivated by the increasing complexity of student financial management in the digital era, which has the potential to encourage consumptive behavior and weak personal financial management. Students are not only required to have academic abilities, but also the ability to manage their finances wisely. This study aims to analyze the influence of financial literacy, locus of control, and parental income on the financial management behavior of students in the Accounting Study Program, Faculty of Economics and Business, University of Mataram. This study uses a quantitative approach with an associative research type. Data were obtained by distributing questionnaires to 278 active students in semesters 2 to 8 who have taken financial management courses using a purposive sampling technique. Data analysis was performed using multiple linear regression with the help of the SPSS program. The results show that financial literacy and parental income have a significant, negative influence on financial management behavior, while locus of control has a positive and significant influence. These findings indicate that self-control is an important factor in shaping better student financial management behavior.